INFORMATION SECURITY AWARENESS LEVEL MEASUREMENT USING MULTIPLE CRITERIA DECISION ANALYSIS (MCDA) - Mukhlis Amin (Puslitbang Literasi dan Profesi SDM Komunikasi dan Informatika, 2014)
This study discusses about information security awareness measurement of civil cervant. Assessment of information security awareness determined using Multi Criteria Decision Analysis (MCDA). MCDA method calculate the total value of some alternatives based on value and weight some criteria. The results showed that information security awareness’s level of civil servant in Government of Makassar is “avarage”. It means action probability required. Keywords: Information Security Awareness (ISA), Multiple Criteria Desicion Analysis (MCDA), Governemnt staff